If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(b + -6) + 4 = 88 Reorder the terms: -6(-6 + b) + 4 = 88 (-6 * -6 + b * -6) + 4 = 88 (36 + -6b) + 4 = 88 Reorder the terms: 36 + 4 + -6b = 88 Combine like terms: 36 + 4 = 40 40 + -6b = 88 Solving 40 + -6b = 88 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -6b = 88 + -40 Combine like terms: 40 + -40 = 0 0 + -6b = 88 + -40 -6b = 88 + -40 Combine like terms: 88 + -40 = 48 -6b = 48 Divide each side by '-6'. b = -8 Simplifying b = -8
| 4.5s-s= | | 0.25-0.6= | | x*3+75=x*9-9 | | 18x11/(18x11)= | | 13m-11=2m+5 | | 2v-1=11 | | 63=2(6x-1)+5 | | 16a-5a= | | d+d+3d= | | -66=6(1+4m) | | 8(4n+2)=240 | | -3(2x-4)+(5x-3)= | | 11h+h= | | 3M-2p=0 | | 6-p^2=47 | | -(4x+6)-3(3x+6)= | | -8+4x=12+9x | | 5(2n-6)=-110 | | LA=3.14(r)(s) | | 4•/•2 | | 8=k+k | | P(X)=22.45 | | 4(5+6r)=116 | | (6-z)(4z-1)=0 | | 6x+15y+5=0 | | O(10)O(n)=2n-1 | | 6p+6+1=13 | | 2(b-1)=5b+1 | | 2(6x+3)=2(x+6) | | 9/0= | | 12y-4y=-128 | | -4=5n-n |